2020
DOI: 10.1111/jce.14838
|View full text |Cite
|
Sign up to set email alerts
|

Women and atrial fibrillation

Abstract: Atrial fibrillation (AF) remains a growing problem in the United States and worldwide, imposing a high individual and health system burden, including increased resource consumption due to repeated hospitalizations, stroke, dementia, heart failure, and death. This comprehensive review summarizes the most recent data on sex‐related differences in risks associated with AF. Women with AF have increased risk of stroke and death compared to men, and possible reasons for this disparity are explored. Women also contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 150 publications
(345 reference statements)
0
43
0
7
Order By: Relevance
“…A review recommends a gendered management strategy in treating AF, as the gender differences in AF are substantial, and antiarrhythmic drugs and ablation can have more complications in females than in males [ 30 ]. However, both the 2020 ESC Guidelines and a recent review recommend that females and males are offered diagnostic assessment and therapies equally [ 6 , 33 ]. It is difficult to conclude on gender differences in risk and benefit of different treatment strategies in AF patients, as females are significantly underrepresented in studies on AF [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…A review recommends a gendered management strategy in treating AF, as the gender differences in AF are substantial, and antiarrhythmic drugs and ablation can have more complications in females than in males [ 30 ]. However, both the 2020 ESC Guidelines and a recent review recommend that females and males are offered diagnostic assessment and therapies equally [ 6 , 33 ]. It is difficult to conclude on gender differences in risk and benefit of different treatment strategies in AF patients, as females are significantly underrepresented in studies on AF [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Atrial fibrillation in women has different characteristics than AF in men with respect to response to treatment, stroke risk, and clinical outcomes. 33 , 34 However, the difference in underlying pathogenesis of AF in women and men has not been fully elucidated. A previous report suggested that estrogen can have a protective benefit against AF, which was shown by substantially less shortening of the effective refractory period in response to rapid pacing in premenopausal women than postmenopausal women or men.…”
Section: Discussionmentioning
confidence: 99%
“…It has been well established that female patients with NVAF are older and more susceptible to stroke than male patients ( 4 , 5 ). Female gender is related to higher mortality and poorer long-term outcome after stroke attack ( 1 , 6 ). Functional outcomes at discharge and 6 months after stroke attack are significantly worse in female patients ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Women with NVAF are generally older than men, with a higher stroke rate. They also have worse long-term outcomes after the stroke attack ( 1 ). Despite their higher stroke risk, women are less likely to be treated with anticoagulation therapy ( 2 ).…”
Section: Introductionmentioning
confidence: 99%